2005
DOI: 10.1103/physrevb.71.180410
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of spin frustration due to orbital selection

Abstract: In order to clarify a crucial role of orbital degree of freedom in geometrically frustrated systems, we investigate both ground-and excited-state properties of the eg-orbital degenerate Hubbard model on two kinds of lattices, ladder and zigzag chain, by using numerical techniques. In the ladder, spin correlation extends on the whole system, while the zigzag chain is decoupled to a double chain and spin excitation is confined in one side of the double chain due to the selection of a specific orbital. We envisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Here we note that O 3g quadrupoles indicate orbital degrees of freedom in the 8 state. In general, orbitals tend to arrange themselves so as to gain the kinetic energy [20], but in 3D environment, ferro orbital order does not easily occur, since the optimal shape of the orbital cannot be determined only from the viewpoint of kinetic energy. Then, orbital (quadrupole) fluctuations significantly remain.…”
Section: Resultsmentioning
confidence: 99%
“…Here we note that O 3g quadrupoles indicate orbital degrees of freedom in the 8 state. In general, orbitals tend to arrange themselves so as to gain the kinetic energy [20], but in 3D environment, ferro orbital order does not easily occur, since the optimal shape of the orbital cannot be determined only from the viewpoint of kinetic energy. Then, orbital (quadrupole) fluctuations significantly remain.…”
Section: Resultsmentioning
confidence: 99%
“…When the Hund's rule interaction is small, the ground state is found to be paramagnetic, 19,20 which is relevant to a geometrically frustrated antiferromagnet. Here, we study the property of the paramagnetic phase and simply ignore the Hund's rule interaction, but the results do not change qualitatively for quarter filling case.…”
Section: Model and Methodsmentioning
confidence: 99%
“…In fact, we have found that orbital ordering actually relaxes the frustration effect in the exchange interaction due to the spatial anisotropy of relevant orbital, even though the lattice originally exhibits a geometrically frustrated structure. 19,20,21 After the occurrence of orbital ordering, one may naively expect that the system is described by an effective spin system on the frozen background of orbital arrangement. It is true that we can intuitively understand what kind of magnetic correlation develops in the static orbital ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Here we refer only the result for J=0, but readers should consult with Ref. [230] about the results for J =0. In Figs.…”
Section: Geometrically Frustrated Systemsmentioning
confidence: 99%